Balancing Robot Berbasis Fuzzy Logic - Sumantri K. Risandriya; Rifqi Amalya Fatekha; Irda Zusmaniar (Politeknik Negeri Batam, 2015)
Balancing robot is in the form of a wheeled robot that has two wheels on the right and left, the robot must be able to maintain a balance. In order to maintain the maximum balance there are many methods that will be used to determine good control optimization to obtain the value of a good response sensor with the motor reactions . At this balancing robot using the method Fuzzylogic with input accellerometer and gyroscope. To get a good response without noise accellerometer use KalmanFilter. The results obtained robot can balance itself with a success rate of 90% and a robot can balance itself despite being disturbed by even encouraged.